TI_GERICHTE 52.2022.200 vom 10. Juni 2022 , Commesse pubbliche. Valutazione dei criteri di aggiudicazione insostenibile - TI Tribunale d'appello (2022)
Commesse pubbliche. Valutazione dei criteri di aggiudicazione insostenibile